GUSELKUMAB AS A NEW BIOLOGIC OPTION FOR THE MANAGEMENT OF ULCERATIVE COLITIS: A NARRATIVE REVIEW - Aleksandra Jagura-Sukiennik; Magdalena Stolarczyk; Julia Bezak; Wojciech Sołtys; Szymon Zysiak; Cezary Kosmecki; Mateusz Stronczyński; Łukasz Deska; Jędrzej Zaguła; Kacper Wicha (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Ulcerative colitis (UC) is a chronic inflammatory bowel disease associated with substantial morbidity and an increasing global burden, for which durable disease control remains challenging despite advances in biologic and small-molecule therapies. Growing evidence implicates the interleukin-23 (IL-23) signaling axis as a key driver of UC pathogenesis, providing a strong biological rationale for selective IL-23 inhibition. This narrative review aims to synthesize the mechanistic basis, preclinical data, and emerging clinical evidence supporting the use of guselkumab, a fully human monoclonal antibody targeting the IL-23p19 subunit, in the treatment of UC.Methods: A comprehensive literature search of the PubMed database was conducted to identify relevant preclinical, clinical, and translational studies evaluating guselkumab in UC, with a focus on pharmacology, efficacy, safety, and clinical positioning.Results: Evidence from the phase 2 and phase 3 QUASAR clinical development program demonstrates that guselkumab provides statistically and clinically meaningful improvements in clinical remission, endoscopic outcomes, and steroid-free disease control in patients with moderately to severely active UC, including both biologic-naive and treatment-experienced populations. Preclinical and mechanistic studies further support its selective and potent inhibition of the IL-23/Th17 pathway, while clinical trials indicate a favorable and predictable safety profile.Conclusions: In conclusion, current evidence positions guselkumab as an effective and well-tolerated advanced therapy for induction and maintenance of remission in moderate-to-severe UC. Ongoing real-world studies, longer-term follow-up, and comparative effectiveness research will be essential to further define its optimal role within evolving treatment algorithms.